Efektivitas Media Visual dalam Meningkatkan Keterampilan Menulis Teks Argumentatif pada Remaja - Anita Candra Dewi (Jurnal Kajian Pendidikan dan Cakrawala Pembelajaran, 2025)
This study aims to examine the effectiveness of using visual media in improving argumentative text writing skills in adolescents. Argumentative text writing skills are one of the important competencies in education, especially in adolescence, which requires critical and argumentative thinking skills. Visual media, such as images, graphics, videos, and infographics, can function as aids in clarifying and enriching the concepts to be written. In this study, various relevant literature studies on the influence of visual media on argumentative writing skills were reviewed. Based on the literature analysis, it was found that visual media can improve understanding, creativity, and argumentation skills in adolescents. In addition, visual media can also help adolescents in compiling clearer and more structured arguments, resulting in more effective argumentative texts. The results of this study indicate that the proper application of visual media can be an effective strategy in improving argumentative text writing skills in adolescents.